Pemanfaatan Limbah Kulit Pisang sebagai Adsorben Alami untuk Menurunkan Kadar Logam Berat Pb(II) dalam Air - Muhamad Rifai; Azhar Hakiki; Linda Rositawati (Pure Chemistry Research, 2025)
Water pollution caused by heavy metals such as lead [Pb(II)] has become a serious environmental issue due to its toxic, persistent, and bioaccumulative nature within the food chain. Various methods have been developed to reduce heavy metal concentrations in water, one of which is adsorption. This study aims to utilize banana peel waste as a natural adsorbent to decrease Pb(II) levels in contaminated water. Dried and ground banana peels were activated with an acid solution to enhance their adsorption capacity, and then applied to test solutions with variations in initial Pb(II) concentration, contact time, and adsorbent dosage. The results showed that banana peels exhibited a significant adsorption capacity for Pb(II) ions, with the highest removal efficiency obtained at an adsorbent dosage of 2 g/100 mL of solution and a contact time of 60 minutes. The adsorption mechanism is presumed to occur through interactions with functional groups such as –OH, –COOH, and –NH2 present in the cellulose, hemicellulose, and lignin structures of banana peels. These findings demonstrate that banana peel waste can serve as an eco-friendly, low-cost natural adsorbent for the treatment of heavy metal–contaminated water.